Retraction: Effect of short-term thiamine supplementation on oxidative stress, inflammation, exercise capacity and prognosis in chronic heart failure: a randomized clinical trial - Geng, Like; He, Sanjun; Wang , Luzhao; Dang , Qun; Wang , Fang; Lv , Guo (Progress in Nutrition, 2023)
Article retracted after publicationhttps://www.mattioli1885journals.com/index.php/progressinnutrition/article/view/13033